Longitudinal Grouping of Target Volumes for Volumetric-Modulated Arc Therapy of Multiple Brain Metastases - Xu, Yingjie; Miao, Junjie; Liu, Qingfeng; Huang, Peng; Ma, Pan; Chen, Xinyuan; Men, Kuo; Xiao, Jianping; Dai, Jianrong (Frontiers in Oncology, 2021)
PURPOSE: When multiple brain metastases (BMs) are treated with single-isocenter volumetric modulated arc therapy (VMAT), unnecessary exposure to normal brain will occur. Here, a longitudinally-grouping method was developed to minimize such unnecessary exposure. MATERIALS AND METHODS: This method has two main aspects: grouping brain lesions longitudinally according to their longitudinal projection positions in Beam’s Eye View (BEV) and rotating collimator to 90°to make MLC leaves conform to the targets longitudinally group by group. For 11 patients with multiple BMs (5-30), two plans were generated by single-isocenter VMAT using longitudinally grouping strategy (LGS) and conventional strategy (CVS). Prescription dose was 52 Gy for 13-fractions. Dose normalization of 100% Dp at 95%PTV was adopted. For plan quality comparison, Paddick conformity (CI) and gradient index (GI) were calculated, and the mean dose and V100%, V50%, V25%, V10% volume of the normal brain were also calculated. RESULTS: There were no significant differences between LGS and CVS plans resulted for CI (p = 0.374), GI (p =0.182) to PTVall, and for V100% (p = 0.266), V50% (p = 0.155) to the normal brain. However, the low dose region in normal brain represented by V25% and V10% significantly reduced for LGS plans (p =0.004, p =0.003, respectively). Consistently the mean dose of the normal brain significantly reduced for LGS plans, reduced from 12.04 Gy (CVS) to 11.17Gy (LGS) (p =0.003). CONCLUSIONS: The longitudinally-grouping method minimizes unnecessary exposure and significantly reduces the total dose to normal brain. And it can be easily used with various treatment planning systems.